Pro .NET 2.0 Windows Forms and Custom Controls in VB 2005 - MacDonald, Matthew (Apress, 2012)
In this book, you’ll learn how to use all of these techniques to design state-of-the-art application interfaces. Best of all, you won’t just learn how to use the existing controls of the .NET Framework—you’ll also learn everything you need to extend, enhance, and customize them.